Menanamkan Konsep Angka Pada Anak Usia Dini Melalui E-Worksheet Berbasis Realistic Mathematics Education (RME) - Merdekawati Hadi, Arnasari; Sriaryaningsyih, Sriaryaningsyih (Griya Journal of Mathematics Education and Application, 2025)
Introducing the concept of numbers to early childhood is done by introducing them through objects around the child. A real approach can encourage children to understand the material more clearly, this is because teachers utilize various real examples that exist around students. As an effort to help achieve these goals, teachers can use e-worksheet based RME to instill the concept of numbers in students. This study was conducted in RA Masyita Bima. Data collection methods used observation and documentation. Data analysis techniques used data collection, data reduction, data display and data verification. The results of the study showed that instilling the concept of numbers in early childhood by using e-worksheet based Realistic Mathematics Education (RME) can increase interest in learning mathematics in early childhood.